South Asia’s Digital Economy : An Opportunity to Build Back Better, Digitally - World Bank (Washington, DC, 2022)
This report provides a region-wide analysis on the status of the digital economy in South Asia. It identifies opportunities and challenges for national and regional action to realize the transformational potential of digitalizing economies, societies, and governments. The report synthesizes and builds upon country assessments produced for Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. It follows the World Bank’s digital economy assessment framework, covering different dimensions of the digital economy from digital infrastructure and public platforms to digital financial services, skills, and the trust environment. It also discusses the opportunities and benefits of regional integration and collaboration. First and foremost, enabling access to high-quality affordable broadband, and increasing its adoption, will yield substantial social and economic benefits. These benefits include better access to information, education, and training, greater administrative efficiency in public services, and improved economic growth and productivity. There are currently significant gaps in connectivity access and usage within and across South Asian countries. While most countries have closed the gaps in mobile network coverage, fixed broadband coverage remains a challenge. The usage gap (represented by the number of people living within range of a mobile network but not using the Internet) remains the region’s biggest challenge, and is driven by gaps in digital literacy, gaps in affordability for the poorest quintiles, and a lack of relevant content and applications. While there is significant diversity across South Asia, countries in the region might consider adopting a twin-track approach as follows: a) implement policies to enhance competition and attract private sector investment for the upgrade and roll out digital infrastructure, especially for fixed fiber networks that connect users over the middle and last miles, and b) invest heavily in demand-side policies and programs to enhance digital skills and increase affordability, especially for the poorest in the region.